Promoting Replicability in Developmental Research Through Meta‐analyses: Insights From Language Acquisition Research. Issue 6 (7th May 2018) - Bergmann, Christina; Tsuji, Sho; Piccinini, Page E.; Lewis, Molly L.; Braginsky, Mika; Frank, Michael C.; Cristia, Alejandrina
Abstract : Previous work suggests that key factors for replicability, a necessary feature for theory building, include statistical power and appropriate research planning. These factors are examined by analyzing a collection of 12 standardized meta‐analyses on language development between birth and 5 years. With a median effect size of Cohen's d = .45 and typical sample size of 18 participants, most research is underpowered (range = 6%–99%; median = 44%); and calculating power based on seminal publications is not a suitable strategy. Method choice can be improved, as shown in analyses on exclusion rates and effect size as a function of method. The article ends with a discussion on how to increase replicability in both language acquisition studies specifically and developmental research more generally. Abstract : The title for this Special Section isMeta‐analysis and Individual Participant Data Synthesis in Child Development, edited by Glenn I. Roisman and Marinus H. van IJzendoorn